Functional Variants Associated With CMPK2 and in ASB16 Influence Bovine Digital Dermatitis - Oelschlaegel, Diana; Wensch-Dorendorf, Monika; Kopke, Grit; Jungnickel, Roswitha; Waurich, Benno; Rosner, Frank; Döpfer, Dörte; Brenig, Bertram; Swalve, Hermann H. (Frontiers in Genetics, 2022)
Bovine digital dermatitis (BDD) is an infectious disease of the hoof in cattle with multifactorial etiology and a polygenic influence on susceptibility. With our study, we identified genomic regions with impact on occurrence and development of BDD. We used 5,040 genotyped animals with phenotype information based on the M-stage system for genome-wide association. Significant associations for single nucleotide polymorphisms were found near genes CMPK2 (chromosome 11) and ASB16 (chromosome 19) both being implicated in immunological processes. An analysis of chromosomal regions revealed polymorphisms rs208894039 and rs109521151 as having significant influence on susceptibility to the disease. Specific genotypes were significantly more likely to be affected by BDD and develop chronic lesions. Our study provides an insight into the genomic background for a genetic predisposition related to the pathogenesis of BDD. Results can be implemented in cattle breeding programs and could pave the way for the establishment of a BDD prescreening test.